The Quality of Teamwork on Methodology in Software Development Workflow - Ibrahim, Zairina; Johar, Md Gapar Md; Rahman, Normy Rafida Abdul (International Journal of Engineering and Technology, 2018)
This paper aims to validate a workflow for software development in process phases to enhance the quality of teamwork. Therefore, dependent on process of software development for projects teams in various phases. However, challenges such as teamwork and information system impede an impact of efficiency development among the teamwork. This paper presents a continuation of an ongoing theoretical framework developed, to further investigate the sustainable and collaborative in teamwork process. To develop the application framework, an approached of user requirement specification (URS), system requirement specification (SRS), layout Module, layout Database, user acceptance testing (UAT) and final acceptance testing (FAT) to completed of phases during the development. Current research on software development on application system is limited to readiness and awareness. This research extends the need for empirical findings from system analyst, top management, developer perception of software development. The paper was validate a process of teamwork in every phases to measure the impact methodology to the workflow and system application. This research found that significantly support the teamwork skill in better performance of application system.